Jurnal akuntansi & auditing Indonesia: VOLUNTARY DISCLOSURE IN INDONESIA: COMPARISON OF SHARIAH AND NON-SHARIAH COMPLIANT COMPANIES - Peni Nugraheni (akuntansi UII, 2011)
Shariah compliant companies are companies which the activities are accordance with Shariah principles. Indonesia, through Bapepam issues Shariah Securities List containing companies which has fulfilled the Shariah requirements issued by regulators. This study attempts to find out the practice of voluntary disclosure of the Shariah compliant companies and identifies the differences with the practice of non-Shariah compliant companies. This research investigates the quantity and quality of voluntary disclosure in the annual reports of Shariah compliant companies listed in Indonesian Stock Exchange and compare it with non-Shariah compliant companies. Voluntary disclosures were measured using 30 items of disclosure index developed by Khomsiah (2005). Based on content analysis of 2009 annual report of 55 Indonesian listed companies for each category, the finding describes the differencse in the quantity and quality of voluntary disclosure value of Shariah and non-Shariah compliant companies